INCREASING BRAND AWARENESS THROUGH DIGITAL CONTENT MARKETING FOR THE SUISTANABILITY OF MSME BUSINESSES FROM NGO PERMAI, PENANG MALAYSIA - Andyan Pradipta Utama; Loeky Rono Pradopo; Agung Hudaya; Renno Reymond Otto Zulfikar (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
The urgency of the implementation of Community Service aims to open the insight of MSME entrepreneurs about the importance of consumers being aware of the existence of products and brands sold by marketers. In the midst of very tight business competition where the increase in digital marketing has made a lot of new entrepreneurs emerge. The number of new entrepreneurs who compete closely with existing entrepreneurs coupled with the declining purchasing power of the public certainly makes people more selective in buying a product. There is a tendency that consumers will choose products that are known both through the experience of using the product and based on information obtained through various sources. Consumers tend to buy products from well-known brands because they feel more comfortable and consider familiar brands to be more reliable, available, easier to find, and unquestionably quality. Therefore, well-known brands are more likely to be chosen by consumers than lesser-known brands. Brand awareness can be created by business actors by creating attractive digital marketing content so that consumers are aware of the existence of a product and brand. The goals and purpose of this community service activity is to provide introduction and also education to the public, especially those who have a business, that digital content marketing can increase brand awareness and support business sustainability. Based on our observation, the adaptation of the digital concept of content marketing and brand awareness carried out by MSMEs under the auspices of the NGO Indonesian Community Organization (PERMAI), Penang Malaysia has not been optimally implemented. The outputs of this research are publications in online media, activity videos, publications in ICCD journals, Posters and IPR.